Correlation Evaluation Scale Through Text Mining Algorithms and Implementation on the Kurdish Language: A Review - Kazheen Ismael Taher; JIHAN Abdulazeez Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
In recent times, because of the many articles that are found on the web, text extraction has become an interesting area of research. Text mining is a technique that can be used to extract useful information or knowledge from text documents that are not typically in an unstructured form. There are some studies conducted to use different techniques of text production for unstructured data sets. This study will provide an overview of the different methods and algorithms that are related to Text mining and also some studies on the mining of Kurdish web documentation. In addition, a collection of research problems and research methodologies will assist scholars in tracking their future research.